Implementation and Analysis of Clustering Techniques Applied on Pocket Switched Network - Muhammad Ali; Mah-Rukh Fida; Ameer Shakayb Arsalaan; Awais Adnan (International Journal of Distributed Sensor Networks)
Clustering is an extraction of closely knitted groups from a set of nodes. Its benefits in social network range from applying marketing schemes on an appropriate interest group to social network analysis. It is also considered an important tool for efficient communication in an intermittent Pocket Switched Network (PSN). Contact probability between mobile devices in disrupted social networks greatly depends upon the mobility profile and level of relationships between the device holders. Unlike flat routing, scalable and efficient routing in these networks is highly dependent upon accurate derivation of social circles or clusters. This paper therefore evaluates existing clustering techniques for terrestrial social network with the end aim of minimizing communication overhead by identifying those message carriers that can bring message closer to destination node. In order to ensure intercluster routing, modification in existing schemes is proposed so as to detect bridge nodes between single hop destination clusters and to find path towards a disjoint destination cluster.